Framework: The channels for indirect impacts - Alan R. Roe; Jeffery I. Round (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper discusses the channels of impact of an extractives activity on an economy by presenting a brief description supported by graphics of the different routes through which the direct economic and social impacts of these activities might be enhanced. These routes include those that often have the highest political profile, namely spending of government revenues. But the paper also discusses other routes and channels that arguably are far more important, such as the direct effects of corporate spend in local supply chains; the immediate 'multiplier' effects of these; the further multipliers that follows from significant wage growth in these supply chains as well as in the main extractive activity; the new downstream activities that may be built on the primary extractive activity; and the externalities that can accrue from the direct boost to skills training that a large extractive investment is likely to provide.
Keywords: B2; Q3; Q4; Q32; O21; 330; extractives; economic impact; multiplier effects